ANALISIS PERBANDINGAN FINANCIAL DISTRESS PADA PERUSAHAAN KONSTRUKSI DI BURSA EFEK INDONESIA TAHUN 2014 – 2018 - Amalia, Rizki Fitri (LPPM STIE Pertiba, 2019)
This study aims to analyze the comparison of financial distress in construction companies in the Indonesia Stock Exchange in 2014 - 2018 using 5 methods are Altman Z-Score, Falmer, Grover, Springate and Zmijewski methods. The sampling technique used was purposive sampling. The sample in this study amounted to 8 construction companies. The analysis technique used is descriptive analysis by comparing the results of financial distress using the 5 methods. The results of the study stated that some companies experienced financial distress or experienced conditions of financial difficulties, such as Adhi Karya (ADHI) and Nusa Konstruksi Enjiniring (DGIK). Financial conditions that are unstable or experience fluctuations that cause companies to have the possibility of financial distress.